Evaluation of in vitro immunostimulatory and cytotoxic effects of recombinant survivin protein in combination with doxorubicin and breast cancer antigen-loaded polycaprolactone nanoparticles - Dinparvar, Sahar; Abamor, Emrah Sefik; Oztav, Sedanur; Inci, Tugba Gul; Ihlamur, Murat; Baghirova, Malahat; Turgut-Balik, Dilek; Allahverdiyev, Adil M. (IOP Publishing Ltd, 2023)
In this study, the immunostimulatory and anticancer activities of the doxorubicin (DOX), MCF-7 and MDA-MB-231 breast cancer antigen-loaded polycaprolactone (PCL) nanoparticles (NPs) in combination with survivin recombinant protein (RP) and an alum adjuvant are evaluated in vitro on J774 macrophage, MCF-7 and MDA-MB-231 breast cancer cell lines. A double-emulsion solvent evaporation method was used for encapsulation of DOX and antigens into PCL NPs. The physicochemical characterization of NPs included size, morphology, zeta potential, release profiles and encapsulation efficiencies, analyzed using scanning electron microscopy, a zeta-sizer and UV-vis spectrometry. The cytotoxic and inhibitory effects of NPs were determined using a methyl thiazolyl tetrazolium assay. Immunostimulatory effects of the NPs were detected by Griess reaction and ELISA tests to determine nitric oxide and cytokine levels, respectively. According to the results, DOX and antigen-loaded PCL NPs ranged between 240 nm and 290 nm. Antigen and drug-loaded NPs appear less toxic over macrophage cells in comparison with non-capsulated free agents. In addition, considerable inhibitory effects of antigen and drug-loaded NPs were observed at non-toxic concentrations, such as 25 and 50 & mu;g ml(-1), on human mammary cancer cell lines (p & LE; 0.0001). The amount of nitrite released from macrophages that were treated with antigen and DOX-encapsulated PCL NPs, in combination with alum and survivin RP, after 96 h incubation was significantly higher than the control, especially at 50 and 100 & mu;g ml(-1), and triggered macrophages to produce high quantities of IL-4 and IL-12 cytokines in contrast to the control. As a result, DOX and antigen-loaded PCL NPs in combination with survivin and alum adjuvant revealed significant immunostimulatory and inhibiting influence on macrophage and breast cancer cells, respectively. The outcomes revealed that antigen and drug-loaded PCL NPs supplemented with survivin RP and an alum adjuvant created an effective platform for the development of nanotechnology-based immunotherapeutic tools to inhibit breast cancer cells. However, these outputs should be supported by further in vivo studies.
Keywords: breast cancer; PCL nanoparticles; doxorubicin; survivin recombinant protein; immunotherapy; NITRIC-OXIDE PRODUCTION; CHEMOTHERAPY; VACCINATION; EXPRESSION; Science & Technology - Other Topics; Materials Science; Physics